ANALISIS PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA ( STUDI KASUS PADA PERUSAHAAN CONSUMER GOODS) - India Bahagia (Politeknik Ganesha Medan, 2024)
This study uses independent variables, namely Current Ratio, Debt to Asset Ratio and Net Profit Margin with the dependent variable namely Profit Growth. The object of research is Consumer Goods companies listed on the Indonesia Stock Exchange for the period 2020 – 2022. The sample selection was carried out using a purposive sampling technique and a sample of 33 companies was obtained. The purposes of this study are: Test and analyze the effect of the current ratio on profit growth during the Covid-19 pandemic in consumer goods companies listed on the Indonesia Stock Exchange for the period 2020 – 2022. Test and analyze the effect of the debt to asset ratio on profit growth during the pandemic covid-19 in consumer goods companies listed on the Indonesia Stock Exchange for the 2020 – 2022 period. Test and analyze the effect of net profit margin on profit growth during the Covid-19 pandemic for consumer goods companies listed on the Indonesia Stock Exchange for the 2020 – 2022 period. After conducting research using the multiple linear analysis method, it can be concluded: 1. Current Ratio (CR) has no effect on company profit growth during the co-19 pandemic. 2. Debt to Asset Ratio (DAR) has no effect on company profit growth during the co-19 pandemic. 3. Net Profit Margin (NPM) has no effect on company profit growth during the co-19 pandemic.